Assessment of Principals’ Performance in Instructional Supervision of Teachers in Public and Private Post- Basic Secondary Schools in Kano Metropolis - IDRIS, Muhammad Kabir (Ilorin Journal of Education, 2024)
The study assessed and examined principal’s performance in instructional supervision for the achievement of effective teaching and learning in public and private post- basic secondary schools in Kano Metropolis as perceived by the principals and teachers. Descriptive survey research design was used. Two null hypotheses were generated and tested, A sample of 346 teachers and 24 principals drawn through a combination of cluster, purposive and random sampling techniques from a population of 7776 teachers and principals in 353 senior secondary schools in the study area. Two validated researcher – developed questionnaires PISPAQ and SBISAQ, whose internal reliability index stood at 0.86 and 0.89 respectively, were used as data collection instruments. One-way analysis of variance was used to analyze the data collected. The result revealed that significant difference exist between principals’ performance in instructional supervision in public and private post – basic secondary schools with private secondary school principals having higher level of performance. It was shown that the frequency of principal’s performance in instructional supervision is a significant predictor of teacher effectiveness regardless of other school factors such as class - size, modern technologies, teacher’s professional qualification. On that basis, it was concluded that, Principal of public schools should put more efforts on instructional supervision of teachers as a means of bridging the achievement disparity between their students and that of private secondary schools. Based on the findings of the study, It was recommended that principal’s instructional supervision should be intensified in all post-basic secondary schools as preventive measure against raising teachers’ ineffectiveness.